Educational policy conditions in multicultural environment - Shafranska-Gajdzica Anna (Borys Grinchenko Kyiv Metropolitan University, 2016)
Policy is a concept that is constantly in the science review. The policy is described as the art of managing and reconciling the interests of different social groups and at the same time seen as a kind of strategy game, which is the foundation of victory and defeat. It is important to understand that there is no political system, even quite democratic, which can provide all things to all people. Realizing certain political action is always preferred one over the other interests. An important element of the policy is its axiological component associated with the creation of specific ideas, ideologies and political doctrines that define the world view of a particular point of view. The functioning of political power often provokes conflicts which arise from the need to protect their own dignity, their own belief systems and beliefs of others. Educational policy is based on adequate knowledge to implement arts education management that enables consideration of interests of different social groups. The mechanisms for implementing educational policy in a multicultural environment are required special attention.